Penggunaan Capital Asset Pricing Model (CAPM) untuk Menilai Kelayakan Investasi pada Saham Indeks IDX30 di Bursa Efek Indonesia (BEI) Tahun 2019-2023 - Febi Amelia Putri; Nurman Nurman; Annisa Paramaswary Aslam; Anwar Ramli; Anwar Anwar (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to assess the feasibility of investing in stocks included in the IDX30 index using the Capital Asset Pricing Model (CAPM). By analyzing 53 stocks from various industries categorized on the Indonesia Stock Exchange (IDX). through historical stock data for the period 2019 to 2023, this study evaluates individual return (Ri), systematic risk (beta/β), and expected return or E(Ri). The analysis results show that overall these stocks provide a positive return of 0.00658 which indicates that these stocks are profitable for investors. However, there were 19 stocks that experienced negative returns, where the stock of PT Waskita Beton Precast Tbk. (WSBP) recorded the lowest return of -2.511%. In contrast, the stock of PT Bank Jago Tbk (ARTO) recorded the highest return of 15.902%. In terms of systematic risk, the majority of stocks have beta values less than 1 (β < 1), indicating that these stocks are defensive in nature with low correlation to the market. Based on the grouping using CAPM, 25 stocks are categorized as undervalued stocks that are worth buying and retaining, while the other 28 stocks are categorized as overvalued stocks that should be avoided or sold by investors. This research provides guidance for investors in making investment decisions based on CAPM analysis.